Evaluasi Program Professional Development di TK-SD XYZ Menggunakan Konsep Trilogi Kualitas Ditinjau dari Perspektif Alkitabiah [An Evaluation of The Professional Development Programme in XYZ Kindergarten and Primary Using the Concept of The Trilogy of Quality Viewed From The Biblical Perspective] - Yemima Handoyo; Linda Liana; Novia Purnomo; Ngatmiati Ngatmiati (Universitas Pelita Harapan, 2021)
Covid-19 brings a significant change in education practice. Due to school closure during the pandemic, teachers must adapt to distance learning implementation. Even in the abrupt change, schools must maintain the quality of education. The previous research proves that Professional development plays a significant role in improving teacher’s competency and performance. As front liner in the education field, improvement of teacher’s competencies and performance will impact the quality of the school. In this essay, professional development during the pandemic situation in TK-SD XYZ will be evaluated using The Juran Trilogy. First, The Juran Trilogy is analyzed using systematic theology approached. The result illustrated that The Juran Trilogy is linier with biblical Christian worldview. The purpose of this evaluation is to ensure how TK-SD XYZ performs quality management practice to maintain its quality during the pandemic situation. This evaluation finds that TK-SD XYZ has applied The Juran Trilogy concept. The practice of quality management in the professional development program in TK-SD XYZ brings a positive impact in increasing customer satisfaction in distance learning practice.